2020
DOI: 10.1001/jamasurg.2019.4613
|View full text |Cite
|
Sign up to set email alerts
|

Association of Autofluorescence-Based Detection of the Parathyroid Glands During Total Thyroidectomy With Postoperative Hypocalcemia Risk

Abstract: Because inadvertent damage of parathyroid glands can lead to postoperative hypocalcemia, their identification and preservation, which can be challenging, are pivotal during total thyroidectomy. OBJECTIVE To determine if intraoperative imaging systems using near-infrared autofluorescence (NIRAF) light to identify parathyroid glands could improve parathyroid preservation and reduce postoperative hypocalcemia. DESIGN, SETTING, AND PARTICIPANTS This randomized clinical trial was conducted from September 2016 to Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
147
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(183 citation statements)
references
References 21 publications
16
147
4
Order By: Relevance
“…Although the French studies reported less hypocalcemia, as defined as <8 mg/dL on POD#1 and 2, 8,19 the Argentinian study showed less severe (<7.6 mg/dL) hypocalcemia with the use of NIFI 20 . None of the studies showed any differences in long‐term hypocalcemia rates 8,19,20 . In the current study, the mean number of parathyroid glands recognized intraoperatively was the same between the NIFI and conventional surgery groups and 1/3 of the parathyroid glands were seen on NIFI first before they became apparent to the eye.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…Although the French studies reported less hypocalcemia, as defined as <8 mg/dL on POD#1 and 2, 8,19 the Argentinian study showed less severe (<7.6 mg/dL) hypocalcemia with the use of NIFI 20 . None of the studies showed any differences in long‐term hypocalcemia rates 8,19,20 . In the current study, the mean number of parathyroid glands recognized intraoperatively was the same between the NIFI and conventional surgery groups and 1/3 of the parathyroid glands were seen on NIFI first before they became apparent to the eye.…”
Section: Discussioncontrasting
confidence: 60%
“…Furthermore, there is a suggestion that there was less incidence of inadvertent parathyroidectomies and parathyroid autotransplantations with NIFI versus conventional surgery 8,19 . Although the French studies reported less hypocalcemia, as defined as <8 mg/dL on POD#1 and 2, 8,19 the Argentinian study showed less severe (<7.6 mg/dL) hypocalcemia with the use of NIFI 20 . None of the studies showed any differences in long‐term hypocalcemia rates 8,19,20 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In addition, ICG has most recently emerged as a technique for assessing the vascularization of the parathyroid glands, which seems to be closely correlated with parathyroid function, after thyroid resection [22,[32][33][34][35][36]. From a technical point of view, the protocols and doses of dye used for ICG angiography differ from center to center, with the best dosage still under debate.…”
Section: Discussionmentioning
confidence: 99%